Evaluation of three enrichment broths and five plating media for Salmonella detection in poultry - Mores Rall, Vera Lúcia [UNESP]; Rall, Ricardo [UNESP]; Aragon, Lina Casale [UNESP]; Da Silva, Márcia Guimarães [UNESP] (My University, 2005)
We evaluated the effectiveness of Selenite Cystine (SC), Tetrathionate Brilliant Green (TBG) and Rappaport Vassiliadis (RV) broths for Salmonella isolation. We also tested three classic plating media, Salmonella-Shigella Agar (SS), Brilliant Green Agar (BGA), Xylose Lysine Desoxycholate Agar (XLD) and two chromogenic agars, Rambach (RA) and CHROMagar Salmonella (CAS). Among 100 poultry carcasses, 29 were positive for Salmonella using all plating media combined. RV broth (69%) and TT broth (58.6%) were more effective than SC broth (24.1%). The chromogenic media gave better results than the classic ones with less false-positive colonies. The most effective isolation medium was CHROMagar, where Salmonella was identified in 23 (79.3%) of the 29 positive samples, followed by Rambach (48%). Positivity for Salmonella using classic media was 13.8% for BGA, 27.6% for SS and 34.5% for XLD.
Keywords: Plating media; Poultry; Salmonella; Selective enrichment